The optimization of asset liability management in mitigating operational risk - Dian Nuriyah Solissa (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
The idea of this research is to analyze the asset and liability management function to maximize the net income of Islamic banking in the era of digitalization and to minimize digital risk as a part of operational risk. The object of this research is the Islamic Bank in Indonesia with the amount of 10 banks. The analysis of the data presents the condition of the asset and liability component of 10 banks and the growth of net income. Afterward, the solver program applies linear programming to acquire high net income with low risk of operational risk. Islamic banking will achieve the minimum growth of operational risk about 11,26% and attain the maximum net income when they eager to enhance their liability, equity, and temporal syrkah fund.